The Heraclitus of Eryximachus at the Symposium 186e4-187c4: A heraclitean medicine - de Campos, Rogério G. (Sofia, 2022)
The physician Eryximachus, represented by Plato in the Symposium, mentions the philosophy of Heraclitus, highlighting a hypothesis of what Heraclitus meant when he opposes agreement and disagreement. The tangle of problems that emerge from this quote does not lend itself to definitive answers, however, here we will approach some elements collected in the Hippocratic treatise On Regime (De victu) 4-6, and in the pseudo-Hippocratic treatise De alimento that suggest a plausible interpretative line for this mention of Heraclitus and this Heraclitism applied to medicine.ResumoO médico Erixímaco, representado por Platão no Banquete, faz uma menção à filosofia de Heráclito, destacando uma hipótese do que Heráclito talvez desejasse dizer quando opõe concordância e discordância. O emaranhado de problemas que dessa citação emergem não se presta a respostas definitivas, entretanto aqui aproximaremos alguns elementos colhidos no tratado hipocrático Da dieta (De victu) 4-6 e do pseudo-hipocrático Do nutriente (De alimento) que sugerem uma linha interpretativa plausível para essa menção sobre Heráclito e esse heraclitismo aplicado à medicina.
Keywords: Eryximachus; Hippocrates; Symposium; De victu and De alimento